The dialectical unfolding of paradigmatic and narrative thinking in a Chinese-as-a-foreign-language classroom. Issue 4 (1st October 2020) - Lee, Sheng-Hsun
ABSTRACT: How do language instructors fulfill institutional mandates while also nurturing students' interest? What becomes of this process when it unfolds not in one class meeting but in a series of pedagogical events? Classroom research has suggested the importance of integrating authentic, conversational, and rapport-building talk with instructional practices. What remains unknown but central to classroom practices is the temporal, institutional, and psychological underpinnings this integration entails. This ethnographic study explores the dialectical unfolding of paradigmatic and narrative thinking in a course of domestic U.S. students and international Korean students. Paradigmatic thought is concerned with truth, scientific logic and categorization, which are essential for explaining language features. Narrative thought 'strives to put its timeless miracles into the particulars of experience, and to locate that experience in time and place.' Drawing on classroom recordings, participant interviews, and instructional artifacts, the study shows that ordinary materials designated by the institution to underscore paradigmatic thinking were rendered extraordinary when the instructor and students collaboratively transformed them with interpersonally and interculturally meaningful stories across a chain of pedagogical encounters.